2022
DOI: 10.1038/s41467-022-28728-4
|View full text |Cite
|
Sign up to set email alerts
|

Splicing the active phases of copper/cobalt-based catalysts achieves high-rate tandem electroreduction of nitrate to ammonia

Abstract: Electrocatalytic recycling of waste nitrate (NO3−) to valuable ammonia (NH3) at ambient conditions is a green and appealing alternative to the Haber−Bosch process. However, the reaction requires multi-step electron and proton transfer, making it a grand challenge to drive high-rate NH3 synthesis in an energy-efficient way. Herein, we present a design concept of tandem catalysts, which involves coupling intermediate phases of different transition metals, existing at low applied overpotentials, as cooperative ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
376
0
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 386 publications
(392 citation statements)
references
References 88 publications
10
376
0
6
Order By: Relevance
“…Notably, the j NH3 and FE NH3 values of Cu@C are comparable to those of the most advanced electrocatalysts for NO 3 − electroreduction at high concentrations (≥100 × 10 −3 m). [12,17,20,21,[25][26][27][28][29] The FE NH3 and yield rate of NH 3 for Cu@C with 100 × 10 −3 m NO 3 − decreased by only 3.8% and 13.4% after 20 rounds of successive reactions (Figure S16, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the j NH3 and FE NH3 values of Cu@C are comparable to those of the most advanced electrocatalysts for NO 3 − electroreduction at high concentrations (≥100 × 10 −3 m). [12,17,20,21,[25][26][27][28][29] The FE NH3 and yield rate of NH 3 for Cu@C with 100 × 10 −3 m NO 3 − decreased by only 3.8% and 13.4% after 20 rounds of successive reactions (Figure S16, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The in situ Raman spectra of Co‐S v ‐MoS 2 show a peak at 479 cm −1 stemming from Co‐OOH/Co‐OH bonds (Figure S17, Supporting Information). [ 61,62 ] Figure 4e displays the corresponding Tafel slopes. Co‐S v ‐MoS 2 exhibits a Tafel slope of 128 ± 4 mV dec −1 , which is less than that of RuO 2 (145 ± 6 mV dec −1 ), suggesting superior OER kinetics possibly due to the large ratio of Co 3+ /Co 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…45 Compared with Cu (932.4 eV and 952.2 eV for Cu 0 ), 46 the binding energy of Cu 0 in Cu–Fe 2 O 3 -60 appeared to have shifted slightly in the positive direction, indicating the decreased electron density of metal Cu in Cu–Fe 2 O 3 -60 due to electron loss. 47 Simultaneously, the slight negative shifts ( ca. 0.3 eV for Fe 2p 3/2 and 0.4 eV for Fe 2p 1/2 ) in the binding energy of Fe 3+ in Cu–Fe 2 O 3 -60 compared with CuO-Fe 2 O 3 (710.7 and 724.3 eV) suggested that Cu–Fe 2 O 3 -60 had gained electrons and become an electron-rich body on the Fe 2 O 3 side (Fig.…”
Section: Resultsmentioning
confidence: 96%